Rancang Bangun Sistem Informasi Penyewaan Bus Berbasis Web pada PT XYZ - Azhari, Ozmar; Bili, Wibi Alfari; Isputrawan, M. Fauzi; Honni, Honni; Lee, Francka Sakti (Universitas Bunda Mulia, 2026)
The advancement of Information Technology (IT) has driven business processes to become more efficient and has contributed to improving service quality. However, PT XYZ, a company engaged in bus rental services, still relies on manual record-keeping in its operational activities, which may lead to data inaccuracies, document loss, and delays in generating transaction reports. This study aims to design and develop a web-based bus rental information system to improve the efficiency of booking processes, data management, and reporting. This research adopts a qualitative approach with data collection techniques including interviews, observations, and literature review. The system is developed using the Software Development Life Cycle (SDLC) with the Waterfall model and is designed using Unified Modeling Language (UML). The results show that the developed system is able to facilitate the bus booking process, reduce recording errors, and support faster and more integrated transaction reporting. Therefore, the system can enhance operational effectiveness and improve service quality at PT XYZ.